Rotan Potensial dari Hutan Bukit Lubuk Pekak, Merangin, Jambi - Titi Kalima; Ratih Damayanti; Adi Susilo (Universitas Gadjah Mada, 2019)
Rattan is a potential non-timber forest product. It grows in almost all parts of Indonesia, and has been widely used and traded. Indonesia as the largest rattan producer in the world supplies about 85% of world rattan needs. Bukit Lubuk Pekak Forest is part of the Production Forest Management Unit (KPHP) area, Merangin District, Jambi Province. The threat form rattan exploitation is increasing, especially in the Bukit Lubuk Pekak. Therefore, it is necessary to conduct study on the potency of rattan in that area for future conservation efforts. This study aimed to investigate rattan species in Bukit Lubuk Pekak forest, Merangin District, Jambi Province. Information of the potency of rattan is essential to support rattan industries. To complete data of rattan potency from Sumatra, an exploration in this area was carried out in July 2016 in Bukit Lubuk Pekak Forest. The study was conducted by purpossive sampling. Identification on morphological characteristics of rattan were performed on all parts of plants including fruits and seeds (if available). The results showed that there were four rattan genus in Bukit Lubuk Pekak Forest: Calamus, Daemonorops, Korthalsia, and Plectocomiopsis. They consisted of nine species, namely Calamus caesius, C. exillis, C. insignis var. longispinosus, C. laevigatus, C. tumidus, Daemonorops micracantha, D. didymophylla, Korthalsia flagellaris, and Plectocomiopsis geminiflora. Among the nine species, two species that is Calamus caesius and Daemonorops didymophylla have been cultivated for industry raw materials and drug, respectively.